The Impact of the Minimum Wage on Match Stability - Mario Centeno; Claudia Duarte; Alvaro A. Novo (Institute for the Study of Labor (IZA), 2014)
We explore increases in the nominal minimum wage in a difference-in-differences setting to estimate match survival wage elasticity. The elasticity is negative and larger than one for matches directly affected by minimum wage increases, those with paying below the new minimum wage. The impact of the minimum wage is stronger for young workers and the manufacturing sector, groups with a large and increasing share of low-wage workers. Given the low-wage mobility in the Portuguese labor market and the large share of workers directly affected by the minimum wage increase (reaching almost 18%), these results call for a careful analysis of the set of policies that interfere with low-wage employment.
Keywords: J23; J38; 330; minimum wage; employment and match elasticities; spillover